SATISFACTION WITH THE JOB OF MEDICAL STAFF AT HANOI GENERAL HOSPITAL OF TRADITIONAL MEDICINE IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the job satisfaction of medical staff at Hanoi General Hospital of TraditionalMedicine in 2021 and some related factors.Subjects and Methods: A cross-sectional descriptive study on 200 medical staff working at HanoiGeneral Hospital of Traditional Medicine.Results: The mean score of satisfaction of medical staff was 3.42 ± 0.28. The overall satisfactionrate for health workers’ work was 49.0 %, of which professional improvement has the highest rateof satisfied health workers at 56.5% and the lowest was the management mechanism with 43.0%.There is a statistically significant relationship between the main income factor in the family and theaverage monthly income with the satisfaction of health workers with OR 0.52 and 1.98, respectively(p
Keywords: Satisfaction, medical staff.